ixpeobssim: A simulation and analysis framework for the imaging X-ray polarimetry explorer - Baldini, Luca; Bucciantini, Niccolò; Lalla, Niccolò Di; Ehlert, Steven; Manfreda, Alberto; Negro, Michela; Omodei, Nicola; Pesce-Rollins, Melissa; Sgrò, Carmelo; Silvestri, Stefano (SoftwareX, 2022)
ixpeobssim is a simulation and analysis framework specifically developed for the Imaging X-ray Polarimetry Explorer (IXPE). Given a source model and the response functions of the telescopes, it is designed to produce realistic simulated observations, in the form of event lists in FITS format, containing a strict superset of the information included in the publicly released IXPE data products. The core simulation capabilities are complemented by a full suite of post-processing applications which support the spatial, spectral, and temporal models needed for analysis of typical polarized X-ray sources, allowing for the implementation of complex, polarization-aware analysis pipelines, and facilitating the interoperation with the standard visualization and analysis tools traditionally in use by the X-ray community. Although much of the framework is specific to IXPE, the modular nature of the underlying implementation makes it potentially straightforward to adapt it to different missions with polarization capabilities.